BIOCHEMICAL INDICATORS OF SERUM OF DOGS WITH DIROFILARIASIS - Kryvoruchenko, D. (Scientific Progress & Innovations, 2022)
Dirofilariasis is a widespread anthropozoan disease of carnivores, as well as humans, which are caused by nematodes belonging to the suborder Filariata, family Onchocercidae, genus Dirofilaria. In case of dirofilariasis, the symptoms are initially nonspecific and may be absent for a long time. The degree of manifestation of clinical signs depends on the type of dirofilaries, the degree of intensity of the invasion, the individual susceptibility of the animal, the anatomical location of helminths, secondary changes in the organs. The aim of the study was to establish changes in biochemical parameters in the serum of dogs with parasitism D. immitis, taking into account the intensity of microdirofilariasic invasion. It was found that with the intensity of microdirofilariasis invasion up to 20 larvae in 1 cm3 of dog blood significant changes in the content of total protein, albumin, total bilirubin, creatinine, urea, glucose, phosphorus, potassium, calcium, alkaline phosphatase activity, ALT, AST, GGT not found. At the intensity of microdirofilariasic invasion of 20–40 larvae/cm3 in the serum of infected dogs, an increase in ALT activity by 34.68 % (p<0.05), GGT by 26.75 % (p<0.05) and alkaline phosphatase by 28.11 % (p<0.05). At the same time, the content of total bilirubin increased by 43.73 % (<0.05), creatinine by 18.64 % (p<0.01) and urea by 59.63 % (p<0.001). At the intensity of microdirofilariasic invasion of 40–60 larvae/cm3 in the serum of infected dogs found more significant changes in biochemical parameters, characterized by an increase in the activity of ALT by 54.12 % (p<0.01), AST by 34.84 % (p<0.001), GGT by 35.81 % (p<0.001), alkaline phosphatase 1.79 times (p<0.001), a decrease in total protein by 21.97 % (p<0.001), glucose by 15.09 % (p<0.05), an increase in albumin content by 23.34 % (p<0.01), total bilirubin 2.38 times (p<0.01), creatinine 1.77 times (p<0, 01), urea 3.24 times (p<0.001) and potassium 13.94 % (p<0.05). At the intensity of microdirofilariasic invasion more than 60 larvae/cm3, in the serum of infected dogs found a significant (p<0.001) increase in ALT activity by 3.06 times, AST – 1.74 times, GGT – 1.93 times and alkaline phosphatase – 2.14 times, a decrease in total protein by 34.97 % (p<0.001), glucose by 24 % (p<0.001) and an increase in albumin by 27.56 % (p<0.01), total bilirubin 2.9 times (p<0.001), creatinine 2.19 times (p<0.001), urea 5.46 times (p<0.001), potassium by 20.03 % (p<0.01). The obtained data will allow more effective treatment of dogs with dirofilariasis disease, taking into account the indicators of their infestation with microfilaries.